Molecular aspects of multiple myeloma - Kastrinakis, N.G.; Gorgoulis, V.G.; Foukas, P.G.; Dimopoulos, M.A.; Kittas, C. (Annals of Oncology, 2000)
Multiple myeloma (MM) is a B-cell neoplasm characterized by bone marrow infiltration with malignant plasma cells, which synthesize and secrete monoclonal immunoglobulin (Ig) fragments. Despite the considerable progress in the understanding of MM biology, the molecular basis of the disease remains elusive. The initial transformation is thought to occur in a post-germinal center B-lineage cell, carrying a somatically hypermutated Ig heavy chain (IGH) gene. This plasmablastic precursor cell colonizes the bone marrow, propagates clonally and differentiates into a slowly proliferating myeloma cell population, all under the influence of specific cell adhesion molecules and cytokines. Production of interleukin-6 by stromal cells, osteoblasts and, in some cases, neoplastic cells is an essential element of myeloma cell growth, with the cytokine stimulus being delivered intracellularly via the Jack-STAT and ras signaling pathways. While karyotypic changes have been identified in up to 50% of MM patients, recent molecular cytogenetic techniques have revealed chromosomal abnormalities in the vast majority of examined cases. Translocations mostly involve illegal switch rearrangements of the IGH locus with various partner genes (CCND1, FGFR3, c-maf). Such events have been assigned a critical role in MM development. Mutations in coding and regulatory regions, as well as aberrant expression patterns of several oncogenes (c-myc, ras) and tumor suppressor genes (p16, p15) have been reported. Key regulators of programmed cell death (BCL-2, Fas), tumor expansion (metalloproteinases) and drug responsiveness (topoisomerase II alpha) have also been implicated in the pathogenesis of this hematologic malignancy. A tumorigenic role for human herpesvirus 8 (HHV8) was postulated recently, following the detection of viral sequences in bone marrow dendritic cells of MM patients. However, since several research groups were unable to confirm this observation, the role of HHV8 remains unclear. Translation of the advances in MM molecular biology into novel therapeutic strategies is essential in order to improve disease prognosis.
Keywords: Cell Cycle; cytogenetics; Human herpesvirus 8; Interleukin-6; multiple myeloma; therapy